1982
DOI: 10.1007/bf00605991
|View full text |Cite
|
Sign up to set email alerts
|

The electrocardiographic and anticholinergic effects of trazodone and imipramine in man

Abstract: The electrocardiographic and anticholinergic effects of trazodone (150 mg) and imipramine (75 mg) were investigated in 8 healthy volunteers. Both agents increased the QTc interval and decreased T wave height, but the effects occurred earlier with trazodone (from 30 min onwards) than with imipramine (150 and 180 min after dosing). Both drugs decreased heart rate, imipramine at 30 and 60 min and trazodone at 90 min. After 120 min, heart rate began to increase with imipramine an effect which was not seen with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…On day 15, AMT significantly increased HR (p < 0.001) con sistent with its known anticholinergic effects, whereas TZD caused a significant bradycar dia (p < 0.001). This effect of TZD was also found by Burgess et al [17] in their normal volunteer study. HR with the AMT group remained elevated to the end of the study period, whereas the TZD-induced bradycar dia did not persist.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…On day 15, AMT significantly increased HR (p < 0.001) con sistent with its known anticholinergic effects, whereas TZD caused a significant bradycar dia (p < 0.001). This effect of TZD was also found by Burgess et al [17] in their normal volunteer study. HR with the AMT group remained elevated to the end of the study period, whereas the TZD-induced bradycar dia did not persist.…”
Section: Resultssupporting
confidence: 73%
“…On day 1, there were no significant differ ences between the treatments for Q-T. How ever, TZD significantly increased the Q-Tc-(p < 0.01) consistent with the findings of Burgess et al [17], The effect disappeared on follow-up and could not be demonstrated in a 19-patient, day 1 sample. This finding is probably due to chance.…”
Section: Ecg Changessupporting
confidence: 81%
See 1 more Smart Citation
“…However, this manifestation of trazodone-induced cardiotoxicity has received comparatively little attention. One evaluation suggested that trazodone does not exert effects on the PR interval, whereas another report found acute administration capable of impairing atrioventricular conduction and causing complete heart block (11,12). Inconsistencies might, at least in part, be due to different cardiac effects of acute and chronic trazodone therapy (13).…”
Section: Ja Service and Ws Waringmentioning
confidence: 99%
“…Toxic effects correlate poorly with serum concentrations after trazodone overdose (3,4). Serum concentrations of around 1.2 mg/L are sufficiently high to prolong the QT interval by 25 ms in healthy young people (11). Therapeutic use is associated with a 10-fold inter-individual range of serum concentrations, for example 0.2-2.0 mg/L (14).…”
Section: Ja Service and Ws Waringmentioning
confidence: 99%